Considerations on the environment: translation, communication and characteristics of its language - González Vallejo, Rubén (Estudios de Traducción, 2023)
The environment as a transdiscipline covers a wide range of areas that go beyond its scope of action and has a language with a great capacity for resilience by absorbing terms from any discipline directly or indirectly involved, offering a strong personality in its characteristics to such an extent that it is considered a language for specific purposes. This can be explained, on the one hand, through the speed with which the sciences it covers evolve and, on the other, because it uses terms from different disciplines to study and explain existing phenomena. Therefore, this paper aims to analyse some theoretical considerations on the language and translation of the environment; to offer a linguistic overview of a microcorpus of scientific terms from the science of ecology present in the DICCIOMED, with emphasis on their composition and scientific origin; and to elaborate a classification of the types of definitions offered in both the DLECT and the DICCIOMED